The Molecular Apgar Score: A Key to Unlocking Evolutionary Principles - Torday, John S.; Nielsen, Heber C. (Frontiers in Pediatrics, 2017)
One of the first “tools” used for systematically evaluating successful newborn transitional physiology at birth was the Apgar Score, devised by Virginia Apgar in 1953. This objective assessment tool allowed clinicians to immediately gauge the relative success of a newborn infant making the transition from the in utero liquid immersive environment to the ex utero gas environment in the delivery room during the first minutes after birth. The scoring system, although eponymous, is generally summarized as an acronym based on Appearance, Pulse, Grimace, Activity, and Respiration, criteria evaluated and scored at 1 and 5 min after birth. This common clinical appraisal is a guide for determining the elements of integrated physiology involved as the infant makes the transition from a “sea water” environment of 3% oxygen to a “land” environment in 21% oxygen. Appearance determines the perfusion of the skin with oxygenated blood—turning it pink; Pulse is the rate of heart beat, reflecting successful oxygen delivery to organs; Grimace, or irritability, is a functional marker for nervous system integration; Activity represents locomotor capacity; and, of course, Respiration represents pulmonary function as well as the successful neuro-feedback-mediated drive to breathe, supplying oxygen by inspiring atmospheric gas. Respiration, locomotion, and metabolism are fundamental processes adapted for vertebrate evolution from a water-based to an atmosphere-based life and are reflected by the Apgar Score. These physiologic processes last underwent major phylogenetic changes during the water–land transition some 300–400 million years ago, during which specific gene duplications occurred that facilitated terrestrial adaptation, in particular the parathyroid hormone-related protein receptor, the β-adrenergic receptor, and the glucocorticoid receptor. All these genetic traits and the gene regulatory networks they comprise represent the foundational substructure of the Apgar Score. As such, these molecular elements can be examined using a Molecular Apgar evaluation of keystone evolutionary events that predict successful evolutionary adaptation of physiologic functions necessary for neonatal transition and survival.